Treatment of silence in the psychoanalytic clinic: a wordy discussion of ethics - Rivera Cano, Jesús Ignacio (Pensando Psicología, 2010)
This article presents the results of research “What mortal la langue say (no) could. Foundation of silence in psychoanalysis”, and deals with the silent treatment the patient in clinical work, as this is guided by the rigorous consideration of ethics as a criterion to determine its effectiveness.
Keywords: silence of the patient; clinical; ethics; psychoanalysis